2010
DOI: 10.5194/bg-7-4059-2010
|View full text |Cite
|
Sign up to set email alerts
|

A seasonal study of dissolved cobalt in the Ross Sea, Antarctica: micronutrient behavior, absence of scavenging, and relationships with Zn, Cd, and P

Abstract: Abstract. We report the distribution of cobalt (Co) showing a significant correlation throughout the water column (r 2 = 0.87, 164 samples). A strong seasonal signal for dCo was observed, with most spring samples having concentrations ranging from ∼45-85 pM, whereas summer dCo values were depleted below these levels by biological activity. Surface transect data from the summer cruise revealed concentrations at the low range of this seasonal variability (∼30 pM dCo), with concentrations as low as 20 pM observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
163
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(189 citation statements)
references
References 94 publications
(201 reference statements)
22
163
4
Order By: Relevance
“…The sources and the cycle of the organic Co-binding ligands in the ocean are not well known (Saito et al, 2001(Saito et al, , 2005(Saito et al, , 2010. In the present study, the relative [L] maxima observed within or close to the Chl-a rich layers in the subtropical domain and the northern subantarctic zone (stations L1, S1, L2, S2; int.…”
Section: Cycle Of the Organic Ligands Along The Sectionmentioning
confidence: 79%
See 4 more Smart Citations
“…The sources and the cycle of the organic Co-binding ligands in the ocean are not well known (Saito et al, 2001(Saito et al, , 2005(Saito et al, , 2010. In the present study, the relative [L] maxima observed within or close to the Chl-a rich layers in the subtropical domain and the northern subantarctic zone (stations L1, S1, L2, S2; int.…”
Section: Cycle Of the Organic Ligands Along The Sectionmentioning
confidence: 79%
“…growth by iron and cobalt contained in vitamin B 12 in the Ross Sea during early austral summer (Bertrand et al, 2007). In that latter study, the colimitation could be related to the absence of vitamin B 12 produced by bacteria and archaea during austral spring (Saito et al, 2010), or to a decrease in the biosynthesis of vitamin B 12 due to low cobalt concentrations (Gordon and Sullivan, 2008).…”
mentioning
confidence: 99%
See 3 more Smart Citations